Como a medição de propensão ao risco do candidato a fraqueado pode ser utilizado pela rede franqueadora para melhorar a eficiência de seu processo de seleção - Oliveira Neto, Ubirajara Marques de (2009)
It is well-known the franchising market growth and the amount of franchised companies established in Brazil in the recent years. This growth, amongst other factors, comes from the great number of entrepreneurs whom have opted to this business model as a strategy for the acquisition of the first own business or for the expansion of the existing ones. In this context, it is necessary to understand the main factors that motivate these entrepreneurs to opt for the acquisition of franchises. The researches about entrepreneurship say that the business risk factor and the individual perception of risk are the main variables that drive the decision for a new business venture. In this context, this research evaluate how the propensity to risk of entrepreneurs who had opted for the acquisition of franchises influenced this decision compared to the typical behavior of investors in financial assets. This text will show that there are no evidences of an economical rationality behavior on the decision process for the acquisition of franchises.